Radiolabeled Cetuximab Conjugates for EGFR Targeted Cancer Diagnostics and Therapy - Wiebke Sihver; Jens Pietzsch; Mechthild Krause; Michael Baumann; Jörg Steinbach; Hans-Jürgen Pietzsch (MDPI AG, 2014)
The epidermal growth factor receptor (EGFR) has evolved over years into a main molecular target for the treatment of different cancer entities. In this regard, the anti-EGFR antibody cetuximab has been approved alone or in combination with: (a) chemotherapy for treatment of colorectal and head and neck squamous cell carcinoma and (b) with external radiotherapy for treatment of head and neck squamous cell carcinoma. The conjugation of radionuclides to cetuximab in combination with the specific targeting properties of this antibody might increase its therapeutic efficiency. This review article gives an overview of the preclinical studies that have been performed with radiolabeled cetuximab for imaging and/or treatment of different tumor models. A particularly promising approach seems to be the treatment with therapeutic radionuclide-labeled cetuximab in combination with external radiotherapy. Present data support an important impact of the tumor micromilieu on treatment response that needs to be further validated in patients. Another important challenge is the reduction of nonspecific uptake of the radioactive substance in metabolic organs like liver and radiosensitive organs like bone marrow and kidneys. Overall, the integration of diagnosis, treatment and monitoring as a theranostic approach appears to be a promising strategy for improvement of individualized cancer treatment.